Validity of the Sock Test for Sitting Balance: A Functional Sitting Balance Assessment. (July 2020) - Franc, Ingrid A.; Baxter, Mary Frances; Mitchell, Katy; Neville, Marsha; Chang, Pei-Fen
There is a relationship between sitting balance and self-care functioning, but no occupation-based sitting balance assessment. The objective of this study was to determine whether the Sock Test for Sitting Balance (STSB) is a valid balance assessment for use by therapists in acute care. Results of the STSB were compared with those of the Adapted Functional Reach (AFR), the Functional Independence Measure (FIM™) chair transfer, and the Kansas University Sitting Balance Scale (KUSBS), in both hospitalized and healthy participants. There is a significant relationship between STSB results and AFR results for all participants ( r s = −.382, p = .012). Relationships between STSB results and score on the FIM™ Chair Transfer subscale ( p = .001), and score on the KUSBS ( p = .003) are significant. The STSB can differentiate between a hospitalized population and healthy population ( p = .017). Criterion and known-groups validity are demonstrated, but should be confirmed with further testing.